HUBUNGAN BEBAN KELUARGA DENGAN KEMAMPUAN KELUARGA MERAWAT PASIEN SKIZOFRENIA DENGAN RISIKO PERILAKU KEKERASAN - Marmisa " "; Jumaini " "; Misrawati " " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
Abstract The purpose of this research is to determine the relationship of the family with the burden of the family's ability to care for schizophrenia patients the risk of violent behavior. The research design is analytic involving 30 respondents. The sampling method use accidental sampling. Measuring instrument use a questionnaire that had been tested for validity and reliability. The analysis use univariate and bivariate. The results based on the characteristics of the respondents indicated that most respondents are at the beginning of the elderly age (46-55 years) of 8 respondents (26.7%), male sex there are 16 people (53.3%), high school graduates there are 12 people (40%). Most of respondents did not work there are 19 people (63.3%) and the relationship with the respondents the most was as a child there are  9 people (30%) and the highest income in one month is <IDR. 2,352,577.25 are 19 people (63.3%). Based on statistical test of chi square obtained p value = 0.010 for cognitive abilities and p value = 0.046 for psychomotor ability, so it can take the conclusion that there is a relationship the burden on families with cognitive abilities and psychomotor abilities families in caring for schizophrenic patients to the risk of violent behavior RSJ Tampan Provinsi Riau. The results of this study recommend research can be used as input for applying mental health education for families who have family members experiencing mental disorders with the topic of family burden with the family's ability to care for patients at risk for violent behavior at home. Keywords: burden of the family, the family's ability.